Analysis of the Effectiveness of the Voluntary Disclosure Program on Taxpayer Compliance at the Koja Pratama Tax Service Office in 2022 - Haysu, Adi Sumarta; Khan, Sadaf (Yayasan Sinergi Kawula Muda, 2023)
This research is motivated by taxpayers' lack of awareness in fulfilling their tax obligations and disclosing their assets in annual tax returns, resulting in decreased compliance levels and tax ratio in Indonesia. The government has implemented a Voluntary Disclosure Program to encourage taxpayers to fulfill their obligations and disclose their assets voluntarily, with the expectation of improving compliance. This study aims to analyze the effectiveness of the program's implementation at the Koja Pratama Tax Service Office in 2022, including identifying inhibiting factors and efforts made to implement the program. Qualitative research methods were used, with primary data obtained from informant interviews and secondary data from interviews, observations, and documentation. The results indicate that while concrete targets have been achieved, they have not significantly impacted taxpayer compliance due to suboptimal target setting and realization. Obstacles faced in implementing the program include limited knowledge of potential participants due to an online mechanism and limited field access for employees. Efforts are being made to maximize data on potential taxpayers to increase participation rates.